Moonlighting of IT Employees - Shree Koteswar, Chaitra (Digital Repository of Theses - SSBM Geneva, 2025)
Moonlighting by IT staff means the work of taking a second job or freelancing apart from the current employment. Practice has recently become more common, particularly in the era of remote working and flexible working arrangements. While moonlighting offers employees the advantage of additional earnings, skills upgrading, and the experience of varied projects, it is also seen as problematic for employers and employees alike. Employers contend that moonlighting could result in diminished productivity, clashes of interest, and intellectual property theft issues because employees could be working for other competing companies or on projects overlapping with their regular job tasks. Employees could also be confronted with the difficulty of balancing time, energy, and mental health from the demands of juggling more than one position. Conversely, moonlighting supporters believe that it can encourage creativity, job satisfaction, and self-improvement, particularly when the secondary work does not conflict with primary job responsibilities. With the changing dynamics of the IT industry, where skill sets are always in demand, the debate around moonlighting also touches upon the blurred lines between personal and professional life in the digital era. This increasing phenomenon demands a reappraisal of work policies, openness, and reciprocal trust among employers and workers to meet the intricacies surrounding moonlighting in the tech sector.